Antipyretic Activity of Avocado Seed (Persea americana) Infusion in Pepton-Induced Fever in Male White Rats Rattus norvegicus - Wilmar Maarisit; Dannari Sampetondok; Reky R. Palandi; Juliani R. Turang; Friska M. Montolalu; Hariyadi Hariyadi; Amal R. Ginting (Biofarmasetikal Tropis (The Tropical Journal of Biopharmaceutical), 2025)
Avocado seeds (Persea americana) have long been used in traditional medicine and are empirically believed to reduce fever. This study aimed to evaluate the antipyretic activity of an avocado seed infusion in male white rats (Rattus norvegicus) induced with peptone. The infusion was prepared using distilled water at 90 °C. The antipyretic test consisted of five groups: a negative control (Na-CMC), a positive control (paracetamol), and three treatment groups receiving avocado seed infusion at doses of 100, 200, and 300 mg/200 g body weight. Fever was induced by intramuscular injection of 5% peptone (1 mL/200 g body weight). Rectal temperature was recorded at 30-minute intervals for 3 hours. The results showed that all treatment doses reduced rectal temperature after 180 minutes. The greatest reduction was observed at a dose of 300 mg/200 g body weight, with a decrease of 2.16 °C, indicating that avocado seed infusion exhibits dose-dependent antipyretic activity.